Examining the Effect of Financial Markets Shocks on Financial Stability in South Africa - Hlongwane, Tshembhani M.; Sheefeni, Johannes P. S. (International Journal of Economics and Financial Issues, 2022)
The paper analyzed the impact of financial market shocks on financial market stability. The goal was achieved by employing quarterly time-series data spanning from 2003:Q1 to 2020:Q4. The study used various econometric techniques such as stationarity, determining optimal lag length, cointegration analysis, estimating a vector error correction model, impulse response functions and forecast error variance decomposition. Following this, the long run relationship amongst the variables was established. The findings revealed that inflation has a negative impact on financial stability in both the short and long run. Lastly, it was only the shocks in economic activities that was found to have a significant impact on financial stability.